Smart materials for tissue engineering : fundamental principles - Wang, Qun (UK: The Royal Society of Chemistry, 2017)
This book focusses on the fundamental principles and recent advances in the materials science developed for tissue engineering purposes.--
Smart Design of Materials for Tissue Engineering; Smart Surfaces Chemistry and Coating Materials for Tissue Engineering; Protein-Based Stimuli Responsive Materials for Tissue Engineering; Stimuli-Responsive Hydrogels for Tissue Engineering; Self-Assembled Biomaterials for Tissue Engineering; Natural Materials as Smart Scaffolds for Tissue Engineering; Engineering Stem Cell Niche and Stem Cell-Material Interactions; Smart Biomaterials with SMart Surfaces for Stem Cell Culture; Conducting Polymers as Smart Materials for Tissue Engineering; Silica Materials as Smart Scaffolds for Tissue Engineering; Functional Nucleic Acid Incorporated Materials for Cell Therapy and Tissue Engineering; Smart Carbon Nanotubes and Graphenes for Tissue Engineering; Smart Functional Porous Materials for Tissue Engineering; Smart Nanofibrous materials for Tissue Engineering; Thermosensitive Biomaterials in Tissue Engineering; Photo-Mediated Biomaterial Scaffolds for Tissue Engineering; Enzyme-Mediated Smart Materials for Tissue Engineering; Magnetic-Responsive Materials for Tissue Engineering and Regenerative Medicine; Magnetic-Responsive Materials as Smart Scaffolds for Stem Cells; Multifunctional Smart Materials for Tissue Engineering; Fabrication of Multifunctional Materials for Cell Transplantation by Microfluidics.
Includes bibliographical references and index.
Text in English.
Keywords: Biomedical materials; Smart materials; Tissue engineering; Tissue Engineering; Biocompatible Materials; HEALTH & FITNESS; HEALTH & FITNESS; MEDICAL; MEDICAL; MEDICAL; MEDICAL; MEDICAL; MEDICAL; Biomedical materials; Smart materials; Tissue engineering